Musik und Dichtung in der "Odyssee" - Albrecht, Michael von (International journal of musicology, 1993)
The author starts from the social functions of music. Then he dwells on the figure of the inspired bard and on the impact of music on the listener. Finally, he attempts to get a new insight into the literary importance of the theme of music within the Odyssey as well as into some of the roots of European musical aesthetics and musicology.
Elektronische Reproduktion der Druckausgabe
Gesehen am 14.06.2023